Unraveling the phylogenetic relationships of Nectouxia (Solanaceae): its position relative to Salpichroa - Carrizo Garcia, Carolina (2017)
Nectouxia (Solanaceae) is a monospecific genus endemic to Mexico and southern United States of America. Morphological and phylogenetic evidence supports a close relationship between Nectouxia and the Andean genus Salpichroa, but the phylogenetic analyses completed to date have included very few Salpichroa species. A comprehensive phylogenetic analysis including Nectouxia and all Salpichroa species was carried out to shed light on the relationship between the two genera. Maximum parsimony and Bayesian inference analyses were done using sequences from three markers (ITS, psbA-trnH, and ndhF-rpL32). The results of both analyses are congruent regarding the strongly supported clades while incongruences are observed in weakly supported clades that can be explained by rapid species radiation. Salpichroa species are divided in two main clades with strong support, while Nectouxia is resolved within one of them. Our results indicate that the two genera should be combined into a single genus or Salpichroa will be paraphyletic as currently circumscribed. The name Nectouxia has priority but the conservation of Salpichroa has been proposed. At the suprageneric level, the Nectouxia + Salpichroa clade is not closely related to Jaborosa, which is further evidence that the previously recognized tribe Jaboroseae is not monophyletic.